Fungal planktonic community related to salinity and temperature in an oligotrophic sea - Asseri, Ashwag A.; Coello-Camba, Alexandra; Agustí, Susana (Frontiers in Microbiology, 2025)
Marine fungi play a crucial role in carbon cycling and food webs by acting as saprophytes or parasites and shaping host communities. However, our knowledge of these fungi in the marine ecosystem remains limited. To address this gap, we conducted a study to investigate the diversity of planktonic fungal communities in the Red Sea, a warm and oligotrophic sea. We collected water samples from the photic layer at six sites along the Red Sea basin and analyzed the fungal community by targeting the 28S rRNA gene. Our results showed that Chytridiomycota dominated these communities, accounting for 85% of reads, followed by members of the divisions Basidiomycota (4.7%) and Cryptomycota (4.13%). Interestingly, we found that fungal communities did not exhibit significant changes with depth or chlorophyll concentration. However, they did vary with the latitudinal gradient in environmental conditions, which is characterized by high temperature (ranging from 22.3 to 27.0°C) and salinity (ranging from 38.0 to 40.4 PSU). Specifically, the proportions of Chytridomycetes and Neocallimastigomycetes (the two dominant classes of Chytridiomycota) were negatively correlated between themselves. Chytridomycetes exhibited a negative correlation with temperature (R2 = 0.60, p = 0.0028) and a positive correlation with salinity (R2 = 0.49, p = 0.010), being more abundant in the northern Red Sea. Conversely, Neocallimastigomycetes showed an increase in abundance with increasing temperature (R2 = 0.61, p = 0.0026) and a decrease with increasing salinity (R2 = 0.40, p = 0.026), making them more prevalent in the southern Red Sea. Overall, our study described a differential distribution of the most dominant fungal classes, with potential significance in their control of planktonic populations and consequent influence in the carbon cycle in the Red Sea ecosystem. These findings underscore the importance of further research to better understand the role of marine fungi in ecosystem functioning.